Die modifizierte subkutan gestielte Lappenplastik: Modified subcutaneously pedicled flap. (November 2015) - Koller, Josef; Hintersteininger, Arno; Brugger-Jentsch, Karin
Summary: The subcutaneously pedicled flap, also known as V‐Y flap, belongs to the group of island flaps whose blood supply (unlike the horizontally perfused advancement and transposition flaps) comes from subcutaneous blood vessels perpendicular to the skin surface. Because of the outstanding perfusion of this type of flap, we remove up to one‐third of the cranial flap pedicle to form a skin flap (3–4 mm thick), resulting in a significant increase in the defect size able to be covered by the V‐Y flap. Moreover, in the infraorbital region – as far as topographically feasible – this flap is pulled further cranially (in the direction of the defect to be closed) by an obliquely placed periosteal suture. This offsets any potential distal tension on the flap and has thus proven beneficial in preventing an ectropion.